Multi-band description of the upper critical field of bulk FeSe - Bristow, M; Watson, M D; McCollam, A; Prentice, J C A; Coldea, A I (University of Oxford, 2023)
This data set was created as a part of the transport and torque measurements to understand the behaviour of the upper critical field of FeSe. These data correspond to the publication with the same name entitled: Multi-band description of the upper critical field of bulk FeSe, by M. Bristow et al. to appear in Physical Review B. The measurements were performed as a function of magnetic fields at constant temperatures using a low temperature cryostat in Oxford and at the High Field Magnet Laboratory (HFML) in Nijmegen up to 35T. This data set contains ASCII files and the different folders and subfolders contain the files corresponding to particular figure and subfigure, respectively. The data were analysed using the WHH model (Phys. Rev.147, 295 (1966)) and the two-band model, as described in Phys. Rev. B 82, 184504 (2010). The Fermi surface was calculated using the Wien2k and using the experimental parameters and the .struct file is provided.